ANALISIS SISTEM PENGENDALIAN INTERNAL PENJUALAN KREDIT, PIUTANG DAGANG DAN PENERIMAAN KAS PADA PT. BINTANG FORTUNA SEJAHTERA - B51109005, ODI SYAFARANDA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The accounting system of a company must be able to provide a guarantee of adequate control procedures in helping the company achieve its goals. The usefulness of the accounting system of the business unit is to identify, merge, classify, analyze, record and report transactions of the business unit and to manage accountability for the related asset. With the demands of more advanced age, employers are increasingly providing credit facilities are attractive to companies that hold development. In evaluating the systems and procedures for credit sales, accounts receivable, and cash receipts on PT. Bintang Fortuna Sejahtera, the authors conducted a study through an analysis tool in the form of a flowchart analysis, internal control questionnaire, compliance test and the substantive test. Based on research conducted by the authors then in general it can be concluded that the sale of loans, accounts receivable, and cash receipts on PT. Bintang Fortuna Sejahtera has been implemented in accordance with the systems and procedures have been established. Key words : Internal Control System Credit Sales, Accounts Receivable and Cash Receipts